Zulu women's music - Joseph, Rosemary (International Library of African Music, 1983)
It is with certain qualifications that this paper is titled “Zulu Women’s Music”. While the ensuing discussion does in fact concern ‘music’, performed by Zulu women in certain areas of KwaZulu, it is not wished to infer that the practices described are necessarily homogeneous throughout the whole of the Zulu-speaking areas of Natal and KwaZulu. The terms ‘music’, ‘song’ and ‘dance’ are used advisedly. There are no direct Zulu equivalents of the Western concepts of music, song and dance; nevertheless these terms are retained in order to facilitate discussion in as much as they refer to broadly similiar Zulu concepts.
Keywords: African Music